Journey through Asia Minor, Armenia and Koordistan in the years 1813 and 1814 with remarks on the marches of Alexander and retreat of the ten thousand. - Kinneir, John Macdonald, Sir, 1782-1830 ([y.y.])
xii, 603 s.